Tracking of objective physical activity and physical fitness in Japanese children - Kensaku Sasayama; Minoru Adachi (BMC Research Notes, 2019)
Abstract Objective The purpose of this study was to examine the tracking of objective physical activity and physical fitness from childhood to adolescence in Japanese children. The longitudinal study comprised 368 participants (aged 9–10 years) in 2008, and the study involved 134 participants (aged 13–14 years, a dropout rate of 63.6%) in 2011. After excluding participants with missing data, a total of 111 participants (46 boys and 65 girls) were available for study. Step counts and moderate-to-vigorous physical activity (MVPA) were measured using a uniaxial accelerometer. Physical fitness was assessed using the following tests: hand grip, sit-ups, sit and reach, side-to-side steps, 20-m shuttle run, 50-m dash, standing broad jump and ball throwing. Results In boys, there was a significant correlation between objective physical activity and all physical fitness tests at baseline and follow-up. In girls, although there was no significant correlation between objective physical activity at baseline and follow-up, all physical fitness tests at baseline and follow-up were significantly correlated. In conclusion, moderate tracking was shown in objective physical activity of boys from childhood to adolescence. In addition, moderate to high tracking was shown in physical fitness of both sexes from childhood to adolescence.